FENOMENA PERNIKAHAN DINI AKIBAT HAMIL PRANIKAH - Mufidati, Khusnul (Ahkam: Jurnal Hukum Islam, 2020)
The phenomenon very disturbing for parents today is the pre-marital relationship. Even though this happens, but parents cannot limit children's relationships. With so many cases of early marriage phenomena due to pregnancy out of wedlock, it is expected that parents give love and more attention to children so that children do not look for love outside. In this study researchers used a qualitative approach. This type of research is descriptive research. The results of this discussion are that every woman who is pregnant before marriage can still get married with the man who impregnated her. Women who are pre-marital and intend to have marriages have the same requirements as virgin marriages (not pregnant) and there will also be no rejection of marriages from the religious affairs office. Unless the bride and groom are not yet old enough, if this happens, the bride and groom must request a marriage dispensation letter at the Local Religious Court. The religious affairs office will not process marriages before the Religious Court issued a marriage dispensation certificate for the bride.